Crystallization Modalities in Polymer Melt Processing Fundamental Aspects of Structure Formation - Janeschitz-Kriegl, Hermann (Springer Vienna : Imprint: Springer, 2010)
The first book to explicitly focus on the processing of crystallizing polymers, it presents innovative research on diverse interfering processes to help clarify the subject. The first to address the unexpectedly strong interaction of three transport phenomena: heat transfer, momentum transfer (rheology) with crystallization kinetics. With many applications, most well-known crystalline structures are found in polymers like high and low density polyethylene, polypropylene, polybutene and their copolymers. Common problems such as anisotropic shrinkage, warping, and split fiber formation are covered. In addition to applications on amorphous polymers, attempts at numerical simulation on crystallizing polymers are also examined. A feeling for the origins of undesired orientations and frozen-in stresses often associated with the manufacturing process is provided to polymer chemists, applied physicists, rheologists, plastics engineers, mold makers and material scientists.